Three smart pals - Rocklin, Joanne; Brunkus, Denise (New York : Scholastic, 1994)
Three friends find humorous solutions to several problems as they spend a sunny afternoon together.
"Cartwheel Books."
3.8
K-3
Keywords: Problem solving -- Fiction; Friendship -- Fiction; Humorous stories; Problem solving -- Fiction; Friendship -- Fiction; Humorous stories